A triphasic nanocomposite with a synergetic interfacial structure as a trifunctional catalyst toward electrochemical oxygen and hydrogen reactions. Issue 11 (23rd February 2021) - Wang, Ying; Yuan, Hongjie; Liu, Fan; Hu, Tianjun
Abstract : Benefiting from the interfacial electron-coupling and synergistic effect among Ag, the CoFe alloy and the N-doped carbon layer, a triphasic interfacial structure Ag–CoFe@NC exhibits superior trifunctional catalytic activity for the ORR/OER/HER. Abstract : Interfacial structure design is an efficient approach to explore efficient heterogeneous catalysts for energy storage and conversion. Herein, a triphasic nanocomposite with the encapsulated Ag–CoFe heterointerface in the graphitic carbon shell is developed via an electronic modulation strategy. The combination of Ag, the CoFe alloy and the carbon layer not only improves charge transfer, but also generates a synergistic effect and more active sites at the interface, significantly boosting the electrocatalytic activity. The obtained catalyst Ag–CoFe@NC-700 exhibits superior trifunctional catalytic activity for oxygen reduction, oxygen evolution and hydrogen evolution reactions (ORR/OER/HER). Interestingly, it reveals remarkable catalytic activity for oxygen electrocatalysis with a low overpotential (0.72 V), and displays good catalytic performance for the HER under alkaline conditions. This work emphasizes the synergy among the components of heterointerfaces and provides a promising strategy to develop advance trifunctional electrocatalysts for Zn–air batteries and water splitting.